Interfacial engineering of printable bottom back metal electrodes for full-solution processed flexible organic solar cells *Project supported by the Research Grant Council of Hong Kong (No. PolyUC5015-15G), the Hong Kong Polytechnic University (No. G-SB06), and the National Natural Science Foundation of China (Nos. 21125316, 21434009, 51573026). (January 2018) - Zhen, Hongyu; Li, Kan; Zhang, Yaokang; Chen, Lina; Niu, Liyong; Wei, Xiaoling; Fang, Xu; You, Peng; Liu, Zhike; Wang, Dongrui; Yan, Feng; Zheng, Zijian
Abstract: Printing of metal bottom back electrodes of flexible organic solar cells (FOSCs) at low temperature is of great significance to realize the full-solution fabrication technology. However, this has been difficult to achieve because often the interfacial properties of those printed electrodes, including conductivity, roughness, work function, optical and mechanical flexibility, cannot meet the device requirement at the same time. In this work, we fabricate printed Ag and Cu bottom back cathodes by a low-temperature solution technique named polymer-assisted metal deposition (PAMD) on flexible PET substrates. Branched polyethylenimine (PEI) and ZnO thin films are used as the interface modification layers (IMLs) of these cathodes. Detailed experimental studies on the electrical, mechanical, and morphological properties, and simulation study on the optical properties of these IMLs are carried out to understand and optimize the interface of printed cathodes. We demonstrate that the highest power conversion efficiency over 3.0% can be achieved from a full-solution processed OFSC with the device structure being PAMD-Ag/PEI/P3HT:PC61 BM/PH1000. This device also acquires remarkable stability upon repeating bending tests.